Cirrhia tunicata ... - Dubatolov, V. V.; Zinchenko, V. K; Ustjuzhanin, P. Ya. (Zenodo, 2023)
Cirrhia tunicata (Graeser, 1890) MATERIAL. Russia: Kunashir Island, Danilovskii kordon, 16-24.IX, 8-14.X 2022, 7 ♂, 12 ♀, 2 ex..; Andreevskii kordon, 25.IX-5.X 2022, 6 ♀, 4 ex. DISTRIBUTION. Russia: Transbaikalia, Amur province, Jewish Autonomous Obleast’, the southern part of Khabarovskii krai, north to the northern limit of broad-leaved forests and the Tumnin River, Primorskii krai (Kononenko, 2016), Sakhalin (Dubatolov et al., 2020); Kyrghyzstan, Kazakhstan, Mongolia, China, Korea, Japan: Hokkaido, Honshu. ... : Published as part of Dubatolov, V. V., Zinchenko, V. K & Ustjuzhanin, P. Ya., 2023, Autumn moths and butterflies (Lepidoptera) new for the fauna of Kunashir Island, pp. 11-24 in Far Eastern Entomologist 474 on page 19, DOI: 10.25221/fee.474.3, http://zenodo.org/record/7945971 ...